Money, culture, class - Bhandari, Parul, author.
1 online resource.
Keywords: Based on ethnographic research, this book explores the ways in which elite women use and view money in order to construct identities - of class, status, and gender. Drawing on their everyday worlds, it tracks the intricate and contested meanings they attach to money. Focusing on weddings, travel, and spirituality, Parul Bhandari delineates the entitlements and privileges as well as the obsessions and vulnerabilities that underlie the construction of class, the shaping of elite cultures, and the curating of femininity. As such, this book offers an innovative account of the interplay between money, modernity, class, and gender.